2014
DOI: 10.5539/gjhs.v6n6p288
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Clustering of Tuberculosis Incidence in the North of Iran

Abstract: Background and Purpose:Tuberculosis (TB) poses a serious threat to public health throughout the world but disproportionately afflicts low-income nations. The aim of this study is to identify the high-risk areas in Mazandaran province (North of Iran) in helping the heath programmer for the best intervention.Materials and Methods:This is an ecological study conducted from 1999 through 2008. The sample included 2444 Tuberculosis (TB) patients. The variables were age, gender, type of disease and residential locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
13
0
7
Order By: Relevance
“…Positive/negative spatial autocorrelation occurs when Moran’s I is close to +1/-1, which indicates that areas with similar (high-high or low-low)/dissimilar (high-low or low-high) incidence of TB are clustered together [ 29 ]. Monte Carlo randomization (9999 permutations) was employed to assess the significance of Moran’s I , with the null hypothesis being that the distribution of TB incidence in Qinghai province is completely spatially random [ 27 ]; in other words, that the counties with high and low TB incidence are randomly distributed across the study area [ 30 ]. If the test is significant ( P ≤ 0.05), this suggests a clustering/dispersing of the TB incidence [ 2 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Positive/negative spatial autocorrelation occurs when Moran’s I is close to +1/-1, which indicates that areas with similar (high-high or low-low)/dissimilar (high-low or low-high) incidence of TB are clustered together [ 29 ]. Monte Carlo randomization (9999 permutations) was employed to assess the significance of Moran’s I , with the null hypothesis being that the distribution of TB incidence in Qinghai province is completely spatially random [ 27 ]; in other words, that the counties with high and low TB incidence are randomly distributed across the study area [ 30 ]. If the test is significant ( P ≤ 0.05), this suggests a clustering/dispersing of the TB incidence [ 2 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Empirical global studies have shown the common environmental (endogenous or extrinsic) risk factor affects TB risk vulnerability are the biophysical or ecological environment, socioeconomic status, human population and demographic characteristic. TB spatial clustering and variation, the high-risk areas are coimpacted by areal proximity or geographical factor [1][2] [12] especially in urban area [1][2] [3], and socio-economic status [2] [3].…”
Section: Tuberculosis In Socio-spatial Dimensionsmentioning
confidence: 99%
“…Previous studies have shown the environmental risk factors in high burden countries of TB can be divided into two main indicators, including ecological environment, human or social environment. The ecological environment is another term of the environment, relating the biotic and abiotic surrounding of an organism or population, For example, TB high-risk prevalence areas are co-impacted by spatial proximity or geographical factor [1][2] [12] especially in urban area [1] [12][3] [38], poor housing quality, crowded and small living condition [14]. Low SES also contributes to the global TB occurrences [2][12] such as unemployment, low educational level and poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Сложная социально-экономическая ситуация и снижение финансирования фтизиатрической службы с начала 90-х гг. XX века, как по России в целом, так и в Республике Крым, привели к ухудшению эпидемиологической ситуации по туберкулезу [3,4,7] Кластерный анализ используется отечественными и зарубежными исследователями для выделения закономерностей развития эпидемического процесса [6,9,10], прогнозирования исходов [2], диагностики туберкулеза [8]. Для анализа эпидемиологии туберкулеза и разработки управленческих решений в системе фтизиатрической службы в Республике Крым представляет интерес использование многомерного анализа для идентификации территорий с однородными показателями здоровья населения по туберкулезу.…”
Section: The Research Objective Is To Study the Epidemiological Situaunclassified